Manajemen Kinerja Guru Di SMP Islam Terpadu Hasanah Kec. Kotarih Kabupaten Serdang Bedagai - Suri Lestari Br Purba; Chaniago, Nasrul Syakur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The teacher is one of the main components in the world of education, to carryout the main tasks in education in charge of teaching and education. Without teachers, activities in educational institutions will not be able to run even educational and teaching activities will stop. Teachers are a central component in educational organizations, therefore the management and performance of teachers must be designed in such a way as to achieve educational goals effectively and efficiently. As a unit in teacher performance management. In simple terms, the main objective of this research is to describe teacher performance management at Hasanah Integrated Islamic Middle School, Kec. Kotarih, Serdang Bedagai Regency. While the specific objectives of this research are to describe: 1) Management of teacher performance planning, 2) Implementation of teacher performance management, 3) Supervision and evaluation of teacher performance management, 4) Opportunities and obstacles in the implementation of teacher performance management. This research method is descriptive qualitative and data collection techniques are interviews, observations, and documentation. The research subjects are school principals, teachers, and stake holders in teacher performance management.